Effect of weight training qualification in aqueous medium for the development of some Physical abilities of the disabled (paralysis of lower limbs is full) Dhafir Harb Ewajela Abstract The research consisted of five sections, namely:Part I included the in - Harb, Dhafir (Journal of Physical Education, 2012)
The research consisted of five sections, namely:Part I included the introduction of research and the importance of using techniques and modern methods in the process of rehabilitation and development of physical abilities of the disabled paralyzed lower limbs is complete and these methods is the use of weight training in the aqueous medium in order to address the problem of research and of lack or scarcity of the use of weight training in the center within the curricula qualification approved and which researcher believes that it will be of much use in the rehabilitative process.The second section Vttriq to weight training in the aqueous medium and the importance of weight training for the disabled, and Part III include research methodology and procedures, where the researcher used the experimental method with the same group and chose the sample intentionally disabled paralysis of lower limbs is complete and the resulting disability from injuries of the spine and confined between lumbar vertebrae fourth until the end of the spine and coming out of the hospital recently after the stability of health status have a constant degree of disability and the number was (6) disabled, then the researcher developed a set of exercises designed to work within the aqueous medium were carried out on the sample after testing Tribal them and after three months of use of the exercises were tested dimensional, and either Part IV has the results of tests and processes statistical tests before and after the sample, where they found significant differences in favor of posterior tests were Menkstha under this section, to be in Part V to reach Alasantajat which was most important of the exercises weightlifting in aqueous media led to the development of physical abilities Alambogesh a (Mtaulp force, Mtaulp speed) and then propose recommendations based on the most important conclusions was the introduction of weightlifting exercises within the curriculum qualifying for this category of the disabled as well as similar studies on samples of various other disabilities .